Studi Penyetelan Relai Jarak Pada Saluran Transmisi 150 KV Menggunakan Software Digsilent - Rusdi Masri; Iswadi Hasyim Rosma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The short circuit disturbance in transmission line can cause supply to disturbance costumers. Therefore, the right protection system is needed to protect transmission line from this disturbance. Analyzed protection equipment in this reseacrh is distance relay protection. In this tool, setting of the right impedance and delay time are very important. Therefore, aim of this reseacrh is to calculate the zone setting (from 1 to 3) and time delay setting of distance relay by using DIgSILENT Power Factory. The setting results from DIgSILENT are compared with manual calculations, found that setting of zone 1, zone 2 and zone 3 are 4,253 Ω, 7,657 Ω and 18,780 Ω, respectively. The time delay settings between zone 1 and zone 2 -3 are (T 2) 0,4 s (T 3) 1,2 s, respectively. As conclusion it has been found distance relay can be operated correctly as expected.Keywords : transmission line, short-circuit, distance relay, DIgSILENT